Kinematic analysis of the supporting leg between different weight divisions in the roundhouse kick of taekwondo - Wang, Y. X.; Kuo, S. Y.; Wang, L. H.; Cheng, K. B. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to compare kinematic differences in the supporting leg between two weight divisions in the Taekwondo Roundhouse Kick. Collegiate Taekwondo athletes participated in the study and differences in maximum joint angles and ranges of motion on the supporting leg during executing the Roundhouse Kick were examined. The results showed significantly larger (p<.05) ankle displacement and less inversion/eversion in the heavy division group during performing the Roundhouse Kick. It is inferred that the strategy adopted by the heavy division group has the tendency of using ankle displacement for achieving a stable ankle angular motion in the supporting foot.